ANALISIS KESALAHAN HURUF KAPITAL DAN TANDA BACA DALAM ESAI SISWA: PENYEBAB DAN SOLUSI - Rizliana, Anisa Silva; Fauzan, Fauzan (Elementar : Jurnal Pendidikan Dasar, 2024)
This study aims to determine the errors of writing capital letters and the use of punctuation in essays made by students. The method used in this research is descriptive qualitative method, which is a method that involves researchers directly to observe the object being studied. Then the data collected from the research results, analyzed according to the aspects of the error and described in the form of words. The data processing used by researchers, namely using the steps of classification, coding, tabulation, correction or correction, calculation, interpretation and inference. The results of this study, it was found that in writing capital letters, the biggest mistakes that students often make are errors in writing capital letters in each word or in the middle of a word in a sentence, with a percentage of 40.1%. One of the factors that cause errors are students who are less trained and lack habituation in writing by paying attention to good and correct linguistic rules. In the use of punctuation marks, the biggest mistake that students make most often is the omission of commas which can be used to avoid misreading or misunderstanding, with a percentage of 67.1%. One of the factors that cause errors is the inaccuracy and ignorance of students in the use or placement of period punctuation and commas to avoid misreading or understanding. There are other factors that cause students to make mistakes in writing capital letters and using punctuation marks because of the low curiosity of students, low motivation to learn and lack of response in learning, and the teacher's lack of familiarity in giving assignments to pay attention to writing capital letters and using good punctuation. and right.